EFFECT OF THE APPLICATION OF RISK MANAGEMENT ON FINANCIAL PERFORMANCE CASE STUDY ON PT. BANK ABG, TBK - Yulianto, Tuk (Program Doktor Ilmu Ekonomi, 2022)
The economic recession that occurred in Indonesia in 2020 due to the Covid-19 pandemic has suppressed the performance of the national banking system. Almost all banking performance indicators experienced a significant decline. This condition also applies to PT. Bank ABG Tbk (ABG Bank) . To mitigate the risk of losses arising from bank business activities, the Financial Services Authority (OJK) since January 2004 has required every commercial bank to implement risk management effectively. This study aims to determine whether the application of risk management at Bank ABG is proxyed by the ratio of Operating Costs to Operating Income (BOPO) for operational risk, the ratio of Non Performing Loans (NPL) for credit risk and Loan to Deposit Ratio (LDR) for liquidity risk. , has a significant effect on the profitability of ABG Bank which is proxy by the ratio of Return on Assets (ROA). This research is a case study, using quantitative methods with secondary data sourced from the financial statements of ABG Bank for 2018-2020 which are accessed directly from ABG Bank. The analysis technique uses multiple linear regression. The results of the study concluded that there was a very high influence between the implementation of Risk Management on Financial Performance and the variable that had a significant effect was Operational Risk (BOPO). Meanwhile, credit risk (NPL) and liquidity risk (LDR) have no significant effect. Keywords: Bank, Risk Management, Financial Performance.